2017
DOI: 10.1111/srt.12417
|View full text |Cite
|
Sign up to set email alerts
|

In vivo reflectance confocal microscopy in daily practice: Image features correlated to histopathology

Abstract: Features correlating well to histopathology are observed on RCM. RCM can be used as an auxiliary diagnosis tool for the clinical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Several non‐invasive diagnostic methods have been proposed as useful tools for skin investigation, 5–12 and in this setting of constantly emerging technologies to assist with medical diagnosis, dermatology distinguishes itself with the promise of high‐definition imaging devices capable of in vivo resolutions approaching those of histopathology. Reflectance confocal microscopy (RCM) and optical coherence tomography (OCT) are among the most used techniques for in vivo evaluation of the skin 13–17 . These techniques have been already proven to be helpful in the diagnosis of skin cancers and inflammatory skin diseases due to their excellent correlation with histopathology 16–25 …”
Section: Introductionmentioning
confidence: 99%
“…Several non‐invasive diagnostic methods have been proposed as useful tools for skin investigation, 5–12 and in this setting of constantly emerging technologies to assist with medical diagnosis, dermatology distinguishes itself with the promise of high‐definition imaging devices capable of in vivo resolutions approaching those of histopathology. Reflectance confocal microscopy (RCM) and optical coherence tomography (OCT) are among the most used techniques for in vivo evaluation of the skin 13–17 . These techniques have been already proven to be helpful in the diagnosis of skin cancers and inflammatory skin diseases due to their excellent correlation with histopathology 16–25 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also have applied a variety of technologies to image abnormal dilated vessels in PWS and compare the changes in images obtained before and after treatment to evaluate the efficacy of treatment. These instruments include structural imaging technologies, such as optical coherence tomography, photoacoustic imaging, reflectance and confocal microscope, as well as functional imaging technologies, such as laser doppler blood flow imaging, laser speckle imaging and space frequency domain imaging 26–31 . However, the accuracy of these technologies for imaging abnormal blood vessels in PWS has not been verified, and they are usually expensive and generally too time‐consuming to be commonly used during outpatient visits.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the usefulness of in vivo confocal microscopy, which correlates well with standard histology, which was first adopted by ophthalmologists, then widespread in dermatology and, recently, has started to be applied in stomatology . In vivo reflectance confocal microscopy (RCM) can real–time image vital tissues scanned from the surface to the submucosa/superficial dermis, on horizontal planes at microscopic resolution, based on the mechanisms of backscattering of light by vital structures with different refractive indexes …”
Section: Introductionmentioning
confidence: 99%